Understanding male enrolment in Malaysian higher education: Analysing individual, social, and economic influences - Zakee, Saadat (2024)
Malaysia is facing gender disparity in higher education institutions, where the proportion of female students surpasses that of male students. According to the data published by the Ministry of Education, this gender gap is transmitted through secondary school, where only 40% of participation is male. This raises significant concerns regarding male students' intentions and implies the necessity to study the factors affecting male students' pursuit of higher education. In this context, a hypothesized model was developed to examine the relationship between these identified factors in the current study. A representative sample of 411 secondary school students was selected for this study. Moreover, the theory of planned behavior is considered a theoretical basis to determine the relationship. The data was analyzed through structured equation modeling (SEM) using Smart PLS. The findings largely supported the model with individual factors, including academic achievement and motivation, showing a significant positive relationship with the attitude of male students towards higher education. Furthermore, career outcome expectancy has a significant positive relationship with male students' intention to seek a university education. The determinants of TPB, including attitude and PBC, have a significant positive relationship with the intention of male students to pursue higher education. The study also demonstrated a significantly positive relationship between three determinants of TPB, including attitude and subjective norm, and the PBC of male students pursuing higher education after school. In contrast, parents' influence and peer influence do not have a relationship with male students' intention to continue higher education; however, when analyzed with subjective norms as a mediator, this relationship between parents' influence and peer influence is fully mediated. The findings of this study significantly contribute towards an existing body of knowledge in understanding the decision factors of male students. Theoretically, the study combines the individual, social, and economic factors with the TPB determinants to assess the theoretical propositions and explain the intention of male students to pursue higher education. Practically, the exploration of the study can guide stakeholders in undertaking collaborative efforts to devise policy parameters that foster motivation, positive attitudes, and promising career prospects for increasing male representation in higher education institutions. Likewise, a collaborative effort to engage parents, community, and society to promote control and social beliefs among male students can develop their intent to pursue higher education. By keeping male students in education, stakeholders can foster the integrity and well-being of educational institutions, thus promoting gender equity among students. Proactively engaging male students in higher education can harness society's social and economic balance.